Solo dwarfs II: the stellar structure of isolated Local Group dwarf galaxies. Issue 1 (9th January 2021) - Higgs, C R; McConnachie, A W; Annau, N; Irwin, M; Battaglia, G; Côté, P; Lewis, G F; Venn, K
ABSTRACT: The Solo ( So litary Lo cal) Dwarf Galaxy survey is a volume-limited, wide-field g - and i -band survey of all known nearby (<3 Mpc) and isolated (>300 kpc from the Milky Way or M31) dwarf galaxies. This set of 44 dwarfs is homogeneously analysed for quantitative comparisons to the satellite dwarf populations of the Milky Way and M31. In this paper, an analysis of the 12 closest Solo dwarf galaxies accessible from the Northern hemisphere is presented, including derivation of their distances, spatial distributions, morphology, and extended structures, including their inner integrated light properties and their outer resolved star distributions. All 12 galaxies are found to be reasonably well described by two-dimensional Sérsic functions, although UGC 4879 in particular shows tentative evidence of two distinct components. No prominent extended stellar substructures, which could be signs of either faint satellites or recent mergers, are identified in the outer regions of any of the systems examined.